IDENTIFIKASI SENYAWA ANTIFUNGI DARI KULIT BATANG KECAPI (Sandoricum koetjape) DAN AKTIVITASNYA TERHADAP Candida albicans - Warsinah Warsinah; Eka Kusumawati; Sunarto Sunarto (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
Kecapi (Sandoricum koetjape (Burm.f.) Merr) was one of the traditional medicine from family Meliaceae and had compounds such as flavonoids, saponins and polyphenols that can be used as antifungal. The objective of this research to know compounds contained from S. koetjape bark that has potential as an antifungal toward C. albicans.Research carried out two stages using extraction by maceration with methanol and fractionation by column chromatography method used the solvent n-hexane, chloroform, ethyl acetate and methanol. The next step was examined its activity toward C. albicans and identification of fraction active compounds with the Gas Chromatograpy-Mass Spectrometry (GC-MS). The results of this research showed that methanol extract from S. koetjape bark had antifungal activity againstC. albicans (39,654%). Next, the methanol extract was fractionated and fractionation results were obtained six fractions with the greatest antifungal activity of fraction III, followed by fraction V (39.66% b/v), fraction IV (39.02% b/v), fraction II (37.91% b/v), fraction VI (35.48 % b/v) and fraction I (33.72% b/v). Identification of compounds with GC-MS in fraction III and compounds contained have potential as an antifungal are α-gurjunene, trans-caryophyllene, aromadendrene, α-humulene, β-caryophyllene, δ-Cadinene, alloaromadendrene, octadecanoic acid (as. stearat), hexadecanoic acid metil ester (metil palmitate), hexadecanoic acid (as. palmitate), 9-octadecenoic acid metil ester (metil elaidate), 9-octadecenoic acid (as. oleat).